The Relationship of Knowledge and Attitude Of Prospective Women With Tetanus Immunization Toxoid Prewedding In The Region Latimojong Health - Warlinda; Nurhasanah; Sriwahyuti (Jurnal Life Birth, 2022)
Premarital TT immunization is TT immunization given to prospective brides before marriage 1 time. The provision of TT immunization can be carried out in health service places such as health centers, posyandu, hospitals, and other health services. The results of the Latimojong Health Center report regarding the coverage of premarital TT immunization in 2020 as many as 45 people, and in 2021, as many as 70 people. This study aims to determine the relationship between the knowledge and attitudes of prospective brides with premarital tetanus toxoid immunization in the Latimojong Health Center area in 2022. The type of research used is quantitative research with a cross-sectional study approach. The sample in this study was all WUS who will get married in August-October 2022 in the Latimojong Health Center Work Area as many as 38 people. Sampling technique using total sampling. The results showed a relationship between the knowledge and attitudes of the bride and groom with premarital tetanus toxoid immunization at the Latimojong Health Center in 2022 with a value of = 0.000 < value = 0.05. It is expected to provide information about tetanus toxoid (TT) immunization for prospective brides in an effort to improve public health.